Arthroscopic Latarjet Learning Curve: Operating Time Decreases After 25 Cases - Shariff K. Bishai, D.O., M.S; Guy R.S. Ball, D.O; Cameron King, D.O; Kenny Ierardi, D.O; Mike Bodine, D.O; Michael Ayad, B.S; Jalen Warren, B.S (Elsevier, 2023)
Purpose: To demonstrate the learning curve associated with the arthroscopic Latarjet procedure and create a timetable to proficiency. Methods: Using retrospective data of a single surgeon, consecutive patients who had an arthroscopic Latarjet procedure performed between December 2015 and May 2021 were initially reviewed for inclusion in the study. Patients were excluded if medical data were insufficient for accurate surgical time record, their surgery was transitioned to open or minimally invasive, or if their surgery was performed in conjunction with a second procedure for a separate issue. All surgeries were performed on an outpatient basis and sports participation was the most common reason for initial glenohumeral dislocation. Results: Fifty-five patients were identified. Of these, 51 met the inclusion criteria. Analysis of operative times for all 51 procedures demonstrated that proficiency with the arthroscopic Latarjet procedure was obtained after 25 cases. This number was determined by 2 methods using statistical analysis (P < .05). The average operative time over the course of the first 25 cases was 105.68 minutes and beyond 25 cases was 82.41 minutes. Male gender was seen in 86.3 percent of the patients. The average age of the patients was 28.6 years old. Conclusions: With continued transition towards bony augmentation procedures for addressing glenoid bone deficiency there is an increasing demand for the arthroscopic bony glenoid reconstruction procedures including the Latarjet procedure. It is a challenging procedure with a substantial initial learning curve. For a skilled arthroscopist there is a significant decrease in overall surgical time after the first 25 cases. Clinical Relevance: The arthroscopic Latarjet procedure has advantages over the open Latarjet approach; however, it is controversial because it is technically challenging. It is important for surgeons to understand when they can expect to be proficient with the arthroscopic approach.